Versatile self-assembly of supramolecular block copolymers with ionic cluster junctions. Issue 19 (25th April 2016) - Cao, Xiao; Zhang, Liying; Xu, Tianyang; Zhang, Shilin; Zhang, Hao; Li, Haolong; Wu, Lixin
Abstract : Clusto-supramolecular block copolymers were prepared by using an inorganic cluster [W6 O19 ] 2− as an ionic junction, which exhibited versatile self-assembly behaviours. Abstract : Clusto-supramolecular block copolymers are synthesized by using an anionic cluster [W6 O19 ] 2− as an ionic junction to link two cationic terminated polystyrene chains. These polymers exhibit versatile self-assembly behaviours not only dependent on the molecular weight but also adaptive to the concentration and temperature.